2018
DOI: 10.1111/hiv.12581
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effectiveness of recommended boosted protease inhibitor‐based antiretroviral therapy in Europe

Abstract: Although confounding by indication and calendar year cannot be completely ruled out, in ART-experienced subjects the long-term effectiveness of DRV/r-containing regimens appears to be greater than that of ATZ/r and LPV/r.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The Nucleosides and Darunavir/Dolutegravir In Africa (NADIA) trial is designed to address two questions. First, whether dolutegravir is non-inferior to darunavir, the best-in-class protease inhibitor drug, 6,7 in a population of patients with high levels of background NRTI resistance switching to second-line therapy. Second, whether maintaining tenofovir in second-line therapy is non-inferior to switching to zidovudine.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…The Nucleosides and Darunavir/Dolutegravir In Africa (NADIA) trial is designed to address two questions. First, whether dolutegravir is non-inferior to darunavir, the best-in-class protease inhibitor drug, 6,7 in a population of patients with high levels of background NRTI resistance switching to second-line therapy. Second, whether maintaining tenofovir in second-line therapy is non-inferior to switching to zidovudine.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…TT has been firmly established as an efficacious and effective treatment option over the last 20 years, both in clinical trials [14] and the real-world setting [15,16]. However, real-world evidence supporting the effectiveness of bPI+3TC, DTG+3TC or DTG+RPV 2DC is limited [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Average adherence in the clinical trial setting is often at least 95% [10,11] while in the real-world it is often below 80% [12] with a significant proportion of patients experiencing treatment gaps [13]. While older TT regimens required 95% adherence for optimal effectiveness [14][15][16], there is currently evidence to support that more contemporary TT regimens are more "forgiving" of suboptimal adherence; indeed, >80% adherence may be enough to maintain suppression [15][16][17].…”
Section: Competing Interestsmentioning
confidence: 99%
“…In a clinical trial that evaluated the long-term effectiveness of ART, the results showed that a DRV-based regimen was superior to an LPV-based regimen in both ART-naive and treatment-experienced patients. The chances of virological failure were lower for DRV compared to LPV when HIV-1 PI therapy was initiated either as a salvage regimen or a switching strategy in treatment-experienced patients [68]. Another study also showed that the use of low dose DRV boosted with ritonavir (RTV) is an efficient switch option to suppress virological failure in patients failing LPV based treatment [69].…”
Section: Discussionmentioning
confidence: 99%